Prefix in Grammatical Meaning of Minang Kabau Language - irhamni, Mutia; Nasution, Khairina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Minang Kabau is a language that is infrequently used in the region of Tembung Village in North Sumatra. To gauge Minang Kabau language's effectiveness, research was conducted using interviews of multiple formants living in the village. The researcher inquired about the use of prefixes in daily communication. The research yielded Minang Kabau prefixes with multifaceted semantic and syntactic functions. Specifically, the prefix /ba/ functions to indicate possession or use of something in verb form, to transform nouns relating to driving and riding into verbs, and to signify production. Additionally, /ba-/ can be considered passive and is equivalent to the prefix /di/. The language features several useful prefix functions, including /paN-/ as a derivational function, /maN-/ which works with nouns, verbs, adjectives, and numbers, /sa-/ which typically combines with words of quantity, /ta-/ indicating involuntary performance and superlative statements, and /ka-/ denoting location. The MinangKabau language utilized by certain individuals has been found to be highly effective. Such findings were discovered by researchers.